Penguatan Kerja Sama Tim dan Literasi Teknologi Robotika Bagi Kalangan Siswa SMA Negeri 2 Kuta di Tengah Transformasi Digital - Marvelino Raymond Sakrabentus; Farel Yiantony; Naya Savina Febriyanti; I Nyoman Yuda Sugiantara; Komang Hari Santhi Dewi; Rifky Lana Rahardian; Ida Ayu Mirah Cahya Dewi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
This community service activity aimed to enhance teamwork skills and exploratory understanding of robotic technology among high school students in responding to the challenges of digital transformation. The activity was conducted at SMA Negeri 2 Kuta as a partner institution, involving 60 students as participants. The implementation was divided into three phases: planning, execution, and evaluation. The method used was project-based training, emphasizing teamwork and hands-on exploration of basic robotic technology. Evaluation was carried out using three main instruments: pre-test and post-test, group performance observation sheets, and student response questionnaires. The results showed that: (1) there was a 67.5% increase in students’ understanding of teamwork, with an average teamwork score of 86 (categorized as very good); (2) students' understanding of robotic technology usage increased by 55.7%, with an average score of 85.05 (categorized as good); and (3) all participants (100%) gave positive responses to the training activities. This activity demonstrates that integrating teamwork training and robotic technology exploration can serve as an effective approach to preparing students for the digital transformation era.